The effect of explicit written corrective feedback on implicit and explicit knowledge / Mitra Samiei Sarkhanlou - Mitra Samiei, Sarkhanlou (2016)
The purpose of this study was three-fold: 1) to examine the general efficacy of different types of WCF on the errors of the target structure (past simple tense) in the short and long term, 2) to compare the possible difference in the effect that different degrees of explicitness of WCF might have on improving the target structure in the short and long term, and 3) to investigate the effect of the different degrees of explicitness of WCF on explicit and implicit knowledge of the past simple tense in the short and long term. One hundred and five EFL Iranian learners participated in this quasi-experimental study. They were divided into four experimental groups (20 in each) that received different degrees of explicit WCF, that is, metalinguistic, direct, indirect, reformulation and a control group (n=20) that did not receive any feedback. The effects of the WCF types were measured by Picture Description Test and Error Correction Test as a pre-test, an immediate post-test, and a delayed post-test. It was found that both metalinguistic and direct WCF could affect the participants’ explicit knowledge of the past simple tense in the short and long term; the indirect WCF on the other hand, could only affect it in the short term and the reformulation was the only kind of WCF that didn’t have any effect on the explicit knowledge of the past simple tense. Moreover, all the experimental groups’ implicit knowledge improved in the short term, but this improvement was sustained in the long term for the metalinguistic and indirect group. So, the results suggest that there was a difference in the effect that different degrees of explicit WCF had on the development of the learners’ explicit and implicit knowledge of the past simple tense. These findings are discussed from the perspective of both